Husband Violence against Married Women in Kerbala Governorate, Iraq - الخفاجي, نبا (Karbala Journal of Medicine, 2019)
Background: Husband violence is an international problematic behavior with grave abuse of civilian privileges that happens between all religious, cultural, economic and social individuals. However, this problem is widely prevalent in under-developed countries with huge mass of media news and discussion about its great impact and sequel in these societies. Literature review showed scarcity of studies on husband violence toward married females in Iraq, especially in Kerbala city. It aims to identify the lifetime prevalence of husband among health center clients and to identify its relationship to socio-demographic variables. Methods: An interview survey was conducted among a cross sectional sample among 320 women (aged 15 to 65 years) attending primary health care centers in Kerbala governorate in Iraq in 2018. A female doctor measured husband violence and potential predictors through interview questionnaire dependent on a World Health Organization questionnaire used in multi-country study. Results: Tow thirds of the sample were exposed to husband violence. The verbal violence was the most common type of husband violence (45.1%) followed by sexual (34.8%) and physical violence (32.8%). Even pregnant women were not spared while all divorced women in the sample were abused. Low economic income significantly raised husband violence which was also associated with husband substance use (smoking, alcohol and other substances). Abused women welcomed any help even by health care personals (64%). Conclusions: Husband violence was very common problem among women in Karbala city and verbal violence was the most common type. The problem needs further large scale investigation and urgent preventive programs to be set through wide community efforts.